A DIGITAL FOOD LITERACY HANDOUT: PROMOTING SUSTAINABLE DIET UNDERSTANDING THROUGH SOCIAL STUDIES LEARNING - Anindyta Fitriyani; Sapriya; Erlina Wiyanarti (Edukasi: Jurnal Pendidikan, 2026)
This research aims to develop a digital food literacy handout to teach students about sustainable diets. This study was done at SMP Telkom Bandung. Research and Development using the ADDIE model is used in this study. Data was collected using questionnaires, tests, and documentation. The Wilcoxon Test, N-Gain Score Effectiveness Test, and descriptive statistical analysis are used. According to research, SMP Telkom Bandung students and social studies teachers need a digital food literacy handout. The digital food literacy handout reflects the social studies curriculum. The Wilcoxon Test yielded Asymp. Sig 2-tailed value of 0.000 is below 0.05. Based on the effectiveness test, the average N-Gain score is 0.72, which is high. This shows that students can gain a more comprehensive understanding of food waste by utilizing a digital food literacy handout. Therefore, the digital food literacy handout can be used in social studies to foster an understanding of sustainable diets.